CREDIT RISK ASSESSMENT OF COMMERCIAL BANKS IN THE DEMOCRATIC REPUBLIC OF CONGO - MATUMUENI NSONA, Jiguelle (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The normal functioning of any company involves interactions with financial institutions. Thus, they often resort to external financing, mainly the bank. In reality, the bank is not totally assured of being reimbursed for any credit granted. It finds itself in various situations, either the credit contracted is not repaid, or it is only partially repaid, or it is not repaid on time. It is this non- payment that is known as credit risk, which is much more random, significant and poorly handled, leading several banks to default. Given that, in the business of commercial banks, the granting of loans is the main activity on the one hand and the non-repayment of these loans being the main risk incurred on the other hand, in this article the objective is to calculate the default rate (TD) and the financial risk of banks by statistical techniques, in particular the coefficients of variation (CV) of the profitability of capital. On a sample of 7 banks, the result shows that the commercial banks established in the Democratic Republic of Congo (DRC) run enormous financial risks which can lead them to bankruptcy.